Effect of rice bran protein hydrolysates on insulin, adiponectin and leptin secretions in rats with metabolic syndrome - Boonloh, Kampeeporn; Pannangpetch, Patchareewan; Kongyingyoes, Bunkerd; Kukongviriyapan, Upa; Tavornchinsombut, Supawan; Kukongviriyapan, Veerapol (Srinagarind Medical Journal, 2013)
Background and Objective: A high carbohydrate or fat diet causes an insulin resistance (IR) and metabolic syndrome (MS). Recently, rice bran diet has been demonstrated to have anti-dyslipidemia, anti-hypertensive and anti-atherogenic properties in obese mice model. In the present study, we investigated the effect of rice bran protein hydrolysates (RBP) on insulin, adiponectin and leptin secretions, which play important role in IR in high carbohydrate-high fat (HCHF) induced MS rats. Method: Male Sprague-Dawley rats weighing 200-230 g were used. The normal control group was fed on chow diet, the MS group was fed on HCHF diet with 5% fructose drinking water for 12 weeks. After that, the MS group was divided into 3 subgroups which were orally administered with RBP 500 mg/kg, pioglitazone 10 mg/kg or distilled water for further 6 weeks. Then, fasting blood glucose (FBG) and serum lipid profiles, insulin, adiponectin and leptin were determined. Result: RBP 500 mg/kg significantly reduced FBG, total cholesterol (TC), triglyceride (TG) and serum leptin as compared to the MS-control group (p<0.05). We found that serum insulin and an indicator of IR, HOMA-IR score of MS rats receiving RBP were significantly lower than that of MS-control (p < 0.05). Interestingly, the levels of adiponectin, an insulin enhancing adipokine, in MS rats receiving RBP and pioglitazone were significantly increased as compared to MS-control group. Conclusion: These results indicate that RBP ameliorates insulin resistance in the MS and could be further developed as novel food supplement for metabolic syndrome patients. Key words: Metabolic syndrome, Insulin resistance, Rice bran protein hydrolysates (RBP).